(3ehTMGJ COhGQ hehGhjd ZfGFjg (B((3ef ebGeGJ eNJdaI(B)s - (3eMeO Hf CHj HcQ GdYUahQj,J (B1103 (3g` s
(3ChdgG (B:s
(3ef cdGe (B"(3CHhHcQ(B" (3GdYUahQi(B: (3Yf ghGc GdPi bO CHGMG s
(3BNQgG (B:s
(3ghjJ GdUOhO Mdh GdJfSi cdeG eQbdJ eG CMdGg jGYPhdi s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B42s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B6 - (3U (B123 s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdeUQjI (B((3afhf LejdI (B435) s
Keywords: (3GdCOHs